Droplet stretching between hydrophobic and hydrophilic plates: Droplet fluid heating. (January 2021) - Al-Sharafi, Abdullah; Yilbas, Bekir S.; Sahin, Ahmet Z.; Al-Qahtani, H.
Abstract: A water droplet stretching vertically in between hydrophobic and hydrophilic plates is considered and droplet heat transfer due to heating from bottom hydrophobic surface is analyzed. The bottom polycarbonate plate surface is hydrophobized through solution immersion technique. The experiments and simulations are repeated for various plates spacings. Findings reveal that the stretching causes necking of the droplet in the top plate region. Droplet heating and stretching cause elongated circulating structures in the vertical direction while increasing velocity in the droplet. The Nusselt number reaches large values prior to droplet stretching and it reduces after stretching. This is related to convection heat transfer from droplet bottom region, which is suppressed by the elongated cell structures under stretching. The Bond number becomes less than one for all plates spacing and the Bond number rises with enhancing droplet volume. Graphical abstract: Unlabelled Image